2020
DOI: 10.1111/geb.13082
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual map of invasion biology: Integrating hypotheses into a consensus network

Abstract: Background and aims Since its emergence in the mid‐20th century, invasion biology has matured into a productive research field addressing questions of fundamental and applied importance. Not only has the number of empirical studies increased through time, but also has the number of competing, overlapping and, in some cases, contradictory hypotheses about biological invasions. To make these contradictions and redundancies explicit, and to gain insight into the field’s current theoretical structure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
133
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(136 citation statements)
references
References 86 publications
3
133
0
Order By: Relevance
“…In contrast, P. sylvestris plantations are usually colonized by numerous shrubs, including P. avium and S. aucuparia, forming dense shrub layers (Zerbe and Wirth 2006). This only partially supports the theory of eco-evolutionary naivety (Ricciardi and Atkinson 2004;Enders et al 2020). Our results rather showed that influences of alien tree species on biodiversity are mediated by their abundance (Kumschick et al 2015), which is positively correlated with functional similarity to native species (Sande et al 2020).…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…In contrast, P. sylvestris plantations are usually colonized by numerous shrubs, including P. avium and S. aucuparia, forming dense shrub layers (Zerbe and Wirth 2006). This only partially supports the theory of eco-evolutionary naivety (Ricciardi and Atkinson 2004;Enders et al 2020). Our results rather showed that influences of alien tree species on biodiversity are mediated by their abundance (Kumschick et al 2015), which is positively correlated with functional similarity to native species (Sande et al 2020).…”
Section: Discussionsupporting
confidence: 44%
“…Eco-evolutionary novelty does not increase impacts of invasive trees Since Darwin's (1859) observations, numerous theories in invasion ecology assumed that success or impacts of invasive species depend on the phylogenetic or functional similarity of alien and native species (Ricciardi and Atkinson 2004;Enders et al 2020). Earlier studies revealed higher impacts of alien species less similar to native species (Ricciardi and Atkinson 2004), but impacts of alien species also depend on species quantity in the ecosystems (Kumschick et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even if recent models suggest that it is not possible to make accurate predictions of the duration of lag phases, in particular for introductions occurring in coastal areas 19 as in the case for M. soledadinus, the apparent lag time for this species is consistent with the existing insect invasion literature. The lag time could in part result from Allee effects, which refer to any process whereby any component of individual fitness is correlated with population size ( 76,77 , also see the reviews of 6,78,79 , which describe the different concepts underlying invasion dynamics). Investigations conducted on populations of M. soledadinus support this idea.…”
Section: Historical Documentation Of the Invasionmentioning
confidence: 99%
“…In consequence, there are a plethora of terminologies, differences in emphasis, and similar ideas are expressed in slightly different formats. Taking the development of hypotheses as an analogy, many hypotheses used to explain aspects of biological invasions overlap, some are vague, and some can be collapsed to general ecological theories that need not be related to biological invasions at all (Catford et al 2009;Enders et al 2020). Furthermore, as only a few hypotheses in invasion science have attracted sustained attention, few hypotheses have consistent and strong evidentiary support (Jeschke et al 2012;Ricciardi et al 2013;Traveset and Richardson 2020).…”
Section: The Origins Purposes and Challenges Facing Framework In Imentioning
confidence: 99%